RESULTS OF MONITORING OF MINERAL METABOLISM DISORDERS IN BOROUGH COWS (Web of Teachers: Inderscience Research, 2025)
This article describes the causes, clinical, physiological, and hematological indicators of mineral metabolism disorders in 8-9-month-old Simmental cows in cattle farms, as well as an analysis of the condition of calves born from them.